2014
DOI: 10.1016/j.meegid.2014.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Sex and rhythms in sandflies and mosquitoes: An appreciation of the work of Alexandre Afranio Peixoto (1963–2013)

Abstract: HighlightsLutzomyia longipalpis in Brazil has recently undergone complex speciation events.Anopheles cruzii in southern Brazil has also undergone recent speciation.The circadian clock mechanisms of both sandflies and mosquitoes have been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The great advantage of D. melanogaster as a model in chronobiology is its well-described molecular mechanisms of the circadian clock and these mechanisms start to emerge also in other Diptera (Codd et al, 2007;Gentile et al, 2009;Rund et al, 2011;Meireles-Filho and Kyriacou, 2013;Kyriacou, 2014a;Gesto et al, 2015;Meuti et al, 2015;Kaiser et al, 2016;Bazalova and Dolezel, 2017;Bertolini et al, 2018;Noreen et al, 2018;Rivas et al, 2018). On the other hand, it is not possible to transfer all clock functions to other insect models as we illustrated above.…”
Section: The Molecular Clock-further Feedback Loopsmentioning
confidence: 99%
“…The great advantage of D. melanogaster as a model in chronobiology is its well-described molecular mechanisms of the circadian clock and these mechanisms start to emerge also in other Diptera (Codd et al, 2007;Gentile et al, 2009;Rund et al, 2011;Meireles-Filho and Kyriacou, 2013;Kyriacou, 2014a;Gesto et al, 2015;Meuti et al, 2015;Kaiser et al, 2016;Bazalova and Dolezel, 2017;Bertolini et al, 2018;Noreen et al, 2018;Rivas et al, 2018). On the other hand, it is not possible to transfer all clock functions to other insect models as we illustrated above.…”
Section: The Molecular Clock-further Feedback Loopsmentioning
confidence: 99%
“…Furthermore, they have undergone rapid speciation colonizing very different habitats all over the world. Their success may be partly due to rapidly evolving clock genes that allowed them to colonize different temporal niches (Kyriacou, ). Particularly interesting is also the pitcher plant mosquito, Wyeomyia smithii , which has undergone an evolutionary transition from blood feeding to obligate nonbiting and at the same time an expansion from the south to the north of North America (Bradshaw et al., ; Merz et al., ).…”
Section: Phylogeny Of Flies (Diptera) With a Special Focus On The Dromentioning
confidence: 99%
“…Thus, the adaptation of the daily activity patterns to different environmental conditions can be easily observed in flies, although individual animals are relatively short‐lived and do usually not experience several seasons (only the individuals that overwinter experience autumn, winter, and spring). The great advantage of studying flies is that the molecular and neuronal mechanisms of the circadian clock are well‐understood in D. melanogaster (see King & Sehgal, this issue) and start to emerge also in other Diptera (Bazalova & Dolezel, ; Bertolini et al., ; Codd et al., ; Gentile, Rivas, Meireles‐Filho, Lima, & Peixoto, ; Gesto et al., ; Kaiser et al., ; Kyriacou, ; Meireles‐Filho & Kyriacou, ; Meuti, Stone, Ikeno, & Denlinger, ; Noreen, Pegoraro, Nouroz, Tauber, & Kyriacou, ; Rivas et al., ; Rund, Hou, Ward, Collins, & Duffield, ). In D. melanogaster , recent studies have shown that M and E activity bouts are reflected by Ca 2+ rhythms in the relevant clock neurons controlling M and E activity, respectively (Liang, Holy, & Taghert, , ).…”
Section: Introductionmentioning
confidence: 99%
“…By studying circadian clock gene expression of Lu . longipalpis , researchers observed an evening peak that anticipated the lights-off cue [ 60 ]. With Ph .…”
Section: Introductionmentioning
confidence: 99%